The natural ventilation performance of traditional Malay house at Rumah Tok Su, Alor Setar, Kedah / Nurul Ainaa Syazana Johari and Izzat Anuar - Johari, Nurul Ainaa Syazana; Anuar, Izzat (2023)
Natural ventilation is one of the passive methods that are necessary to provide indoor air quality. Its helps to gain better indoor air and increase awareness of energy saving. However, the problems related to the hot and humid climate in Malaysia will encounter heat problems that will cause discomfort in the house. Because of that, modern house nowadays prefers to apply mechanical cooling system such as air conditioning in providing thermal comfort. This problem contributes to not only high-energy usage, but it will also prevent ventilation from occurring and make people feel uncomfortable. The traditional Malay house was a good example that provided some space arrangement that was compatible with the local climate and better thermal indoor comfort compared to the modern house. As a result, the aim of this study is to explore how architectural details of traditional houses such as openings, roofs, or affect air movement performance, with the goal of incorporating thermal comfort design elements into modern houses. A case study of traditional Malay house at Rumah Tok Su, Kampung Warisan, Alor Setar, Kedah was chosen. The house shows that orientation of the house and the position of ventilation openings play an important role to determine the indoor air flow performance. The findings of this research are expected to show that passive design strategies such as cross and stack ventilation allow air flow through the house.